2021
DOI: 10.1038/s41598-020-80147-x
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic efficacy of repetitive transcranial magnetic stimulation in an animal model of Alzheimer’s disease

Abstract: Previous studies on repetitive transcranial magnetic stimulation (rTMS) suggested potential neurorestorative properties in Alzheimer’s disease (AD). This study aimed to investigate therapeutic effects of rTMS on an AD mouse model at high and low frequencies. The subject mice were allocated into the AD model group (AD induced by intracerebroventricular amyloid beta 42 oligomer [Aβ42] injection) and the saline-injected control group. Each group was subdivided according to rTMS treatment: high frequency (20 Hz), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Notably, a number of studies have indicated an increase in endogenous neurotrophic content (BDNF) in the affected brain regions after TMS therapy ( 2 , 74 ). BDNF is a neurotrophin involved in synaptic plasticity changes and improves learning, memory and cognitive functions via the BDNF-tropomyosin receptor kinase B (TrkB) signaling pathway ( 32 , 74 ). Therefore, BDNF serves a critical role in memory formation and synapsis.…”
Section: Neurobiological Changes Associated With Tms In Admentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, a number of studies have indicated an increase in endogenous neurotrophic content (BDNF) in the affected brain regions after TMS therapy ( 2 , 74 ). BDNF is a neurotrophin involved in synaptic plasticity changes and improves learning, memory and cognitive functions via the BDNF-tropomyosin receptor kinase B (TrkB) signaling pathway ( 32 , 74 ). Therefore, BDNF serves a critical role in memory formation and synapsis.…”
Section: Neurobiological Changes Associated With Tms In Admentioning
confidence: 99%
“…Furthermore, the expression levels of BDNF are altered in neurodegenerative disorders, for example the BDNF levels are decreased in AD ( 80 ). A study by Choung et al ( 32 ) revealed an increase in BDNF expression, as well as neuronal nuclear protein (NeuN) and neuroepithelial stem cell protein (Nestin), after 20 Hz HF-rTMS compared with the non-rTMS group or sham group in the hippocampus and cerebral cortex regions. It was concluded that rTMS exerted neurogenic and neuroprotective effects and promoted neurogenesis ( Table I ) ( 32 ).…”
Section: Neurobiological Changes Associated With Tms In Admentioning
confidence: 99%
See 3 more Smart Citations